Coumarin Derivative N6 as a Novel anti-hantavirus Infection Agent Targeting AKT - Li, Zhoupeng; Wang, Fang; Liu, Yongsheng; Zhai, Dongshen; Zhang, Xiaoxiao; Ying, Qikang; Jia, Min; Xue, Xiaoyan; Meng, Jingru; Li, Jing; Wu, Xingan; Li, Mingkai (Frontiers in Pharmacology, 2021)
Hantaviruses are globally emerging zoonotic viruses that can cause hemorrhagic fever with renal syndrome (HFRS) in Asia and Europe, which is primarily caused by Hantaan virus (HTNV) infection, results in profound morbidity and mortality. However, no specific treatment is available for this disease. Coumarin derivatives have been reported as antiviral molecules, while studies about the bioactivity of coumarin derivatives against HTNV infection are limited. To study the potential antiviral activity of coumarin derivatives, 126 coumarin derivatives are synthesized, and their inhibitory activity against HTNV is analyzed in vitro. Among these compounds, N6 inhibits HTNV with relatively high selectivity index at 10.9, and the viral titer of HTNV is reduced significantly after 5, 10, and 20 μM N6 treatments. Furthermore, the administration of N6 at the early stage of HTNV infection can inhibit the replication and production of infectious HTNV in host cell, this therapeutic efficacy is confirmed in HTNV-infected newborn mice at the early stage of infection. The molecular docking results show that N6 forms interactions with the key amino acid residues at its active site, and reveals several molecular interactions responsible for the observed affinity, and the treatment of N6 can inhibit the expression of p(Ser473)Akt and HTNV nucleocapsid protein significantly. As such, these observations demonstrate that coumarin derivative N6 might be used as a potential agent against HTNV infection.